Ultrasonic assisted glass bead loaded gas liquid separator-photochemical vapor generation-T-shaped slotted quartz tube-flame atomic absorption spectrophotometry system for antimony determination in tap water and wastewater samples - Yazici, Elif; Buyukpinar, Cagdas; Bodur, Suleyman; San, Nevim; Komesli, Okan Tarik; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2021)
In this study, optimization and validation of ultrasonic assisted glass bead loaded gas liquid separator-photochemical vapor generation-T-shaped slotted quartz tube-flame atomic absorption spectrophotometry (UA-GLS-PVG-T-SQT-FAAS) system was performed for the determination of antimony in real samples. Volatile derivatives of antimony were generated and separated from liquid matrix by combination of a UV photoreactor and gas-liquid separation. Optimization of all variable parameters which effect volatile compound generation and separation efficiency such as low molecular weight organic acid type and concentration, ultraviolet irradiation period, gas-liquid separator design, carrier gas flow rate and sample volume were evaluated one at a time keeping the others constant. Limit of detection and quantification were calculated as 47 and 157 mu g L-1, respectively. Detection power of the developed method was enhanced about 58 folds compared to conventional FAAS system over LOD comparison. In addition, applicability/accuracy of the developed method was checked by spiking experiments in tap and wastewater samples and percent recovery results were found in the range 83.4-106.4%.
Keywords: Antimony; Flame atomic absorption spectrophotometry; Photochemical vapor generation; Tap water; Wastewater; FLUORESCENCE SPECTROMETRIC DETERMINATION; HYDRIDE GENERATION; SENSITIVE DETERMINATION; NATURAL-WATERS; SELENIUM; SPECIATION; EXTRACTION; BEVERAGES; ACID; Chemistry